2021
DOI: 10.1063/5.0057903
|View full text |Cite
|
Sign up to set email alerts
|

Green–white color switchable light-emitting devices based on laterally fused cesium lead bromide perovskite nanowires

Abstract: Inorganic lead halide perovskites are excellent optoelectronic semiconductors; however, little has been known about the characteristics of their nanowire-based light-emitting devices (LEDs). We study the LEDs employing self-assembled CsPbBr3 nanowires as emission layers. They tend to form crystallographic orientation-consistent laterally fused parallel arrays when self-assembling into the emission layer in the device due to Coulomb attraction between such ionic semiconductors. At high nanowire concentration, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Besides the CsPbBr 3 NCs, the corresponding NWs have higher PLQY and lower surface defects, where the light emission of the LED device depends on the concentration of NWs in the EML films. The EML films with a high concentration of NWs exhibit green emission, whereas white emission is observed for the LED devices with low NW concentrations, due to the participation of the carrier transport layer in the recombination process . The LED devices of cyan emitting larger diameter CsPbBr 3 NWs exhibit the maximum luminance and EQE of 96 Cdm –2 and 7.1%, whereas the blue emitting NWs with a lower diameter have luminance and EQE values as 13 Cdm –2 and 0.9%, respectively .…”
Section: Perovskite Optoelectronic Devicesmentioning
confidence: 97%
See 1 more Smart Citation
“…Besides the CsPbBr 3 NCs, the corresponding NWs have higher PLQY and lower surface defects, where the light emission of the LED device depends on the concentration of NWs in the EML films. The EML films with a high concentration of NWs exhibit green emission, whereas white emission is observed for the LED devices with low NW concentrations, due to the participation of the carrier transport layer in the recombination process . The LED devices of cyan emitting larger diameter CsPbBr 3 NWs exhibit the maximum luminance and EQE of 96 Cdm –2 and 7.1%, whereas the blue emitting NWs with a lower diameter have luminance and EQE values as 13 Cdm –2 and 0.9%, respectively .…”
Section: Perovskite Optoelectronic Devicesmentioning
confidence: 97%
“…The EML films with a high concentration of NWs exhibit green emission, whereas white emission is observed for the LED devices with low NW concentrations, due to the participation of the carrier transport layer in the recombination process. 70 The LED devices of cyan emitting larger diameter CsPbBr 3 NWs exhibit the maximum luminance and EQE of 96 Cdm −2 and 7.1%, whereas the blue emitting NWs with a lower diameter have luminance and EQE values as 13 Cdm −2 and 0.9%, respectively. 71 CsPbI 3 also acts as an EML layer in the LEDs depending on the αand δ-phases.…”
Section: Perovskite Optoelectronic Devicesmentioning
confidence: 99%
“…Reproduced with permission. [ 198 ] Copyright 2021, AIP publishing. d) CsPbBr 3 QW arrays‐based spherical LEDs: schematic illustration of the device structure (left), EL image (middle), and angular emission (right) of the spherical device.…”
Section: Optoelectronic Applicationsmentioning
confidence: 99%
“…Wu et al demonstrated a green-white color switchable LED device based on laterally fused CsPbBr 3 NWs. [198] The horizontally aligned perovskite NWs were utilized as the emission layer, as shown in Figure 13c, left. It is interesting that, at high NW concentration, the LED emitted pure-green light, and the carriers transported through Fowler-Nordheim (FN) quantum tunneling and direct injection successively (Figure 13c, middle).…”
Section: Ledsmentioning
confidence: 99%
See 1 more Smart Citation